A conceptual framework of the blockchain technology adoption for zakat institution in Indonesia - Zulfikri, Zulfikri; Kassim, Salina; Othman, Anwar Hasan Abdullah (University of Turin, 2023)
The adoption of blockchain technologies necessitates the consideration of a wide range of factors far beyond the technology focus of most current research. Blockchain technology's ability to record transactions on distributed ledgers opens new possibilities for zakat institutions to improve transparency, prevent fraud, and build trust in the public sector. Even though academic research on blockchain technology is still in its infancy, most academics focus on the technology itself and overlook the zakat institutions adopting it. This paper drew on a comprehensive literature review to propose a conceptual framework for blockchain technology adoption. Zakat institutions can use the proposed framework as a reference point for adopting blockchain applications and for scholars to expand, refine and evaluate research into blockchain technology.